Modeling the Demand for Family and General Takaful in Malaysia (A Comparative Study): ARDL Approach to Cointegration - Weni Hawariyuni; Marhanum Che Mohd Salleh (Institute for Research and Community Empowerment (LPPM TAZKIA), 2012)
Objective- Nowadays, numerous studies focus on the determinant of the demand for takaful, either family or general takaful in Malaysia. In this respect, these studies employ economic and socio-demographic variables to examine the determinants of takaful. They found that income, interest rates, financial development, pensions, stocks, price of insurance, life expectancy, dependency ratio, education, and age have positive on determinants of takaful. However, previous tudies have found that inflation, savings, and unemployment rate have negative relationship with the determinant of takaful in Malaysia. This study attempts to examine the determinants of the demand for family takaful and general takaful for comparative study in Malaysia for the period of 1988 to 2010. It employs economic and socio-demographic variables to measure these determinants.Methods-Using time series data, this study applies the Autoregressive Distributive Lag (ARDL) approach to cointegration to examine the determinants of the demand for family takaful and general takaful in the short and long run.Result-The findings indicate that the economic and socio-demographic variables such as income, and education have positive relationship with the demand for family takaful in the short run, but not in the long run.Conclusion-Meanwhile, it also indicates that income and education have no relationship with demand for general takaful in Malaysia in the short run and long run. It indicates that if there is an increase in income, people tend to buy more family takaful of STMB. At the same time, the educated people already aware of the takaful products, they may necessarily purchase family takaful than life insurance.